Diagnostic performance of ultrasound to differentiate perforated from non‐perforated paediatric appendicitis: A narrative review. Issue 3 (18th August 2020) - Conwell, Nancy K.; Kennedy, Narelle J.; Quinton, Ann E.
Abstract: Appendicitis is the most common reason for urgent paediatric surgery, with significantly higher rates of appendiceal perforation in young children. Distinct management plans are required for perforated and non‐perforated appendicitis and thus accurate differentiation is crucial. Ultrasound is a safe imaging modality that avoids ionising radiation exposure to children and is useful for diagnosis of appendicitis. The aim of this review is to explore the diagnostic performance of ultrasound for detecting perforated paediatric appendicitis and to determine the sonographic findings useful for distinguishing perforated from non‐perforated appendicitis in the paediatric population. Ultrasound demonstrates high specificity ranging from 90% to 100%, but low sensitivity ranging from 23% to 44% for differentiating perforated from non‐perforated appendicitis in children. Sonographic findings significantly associated with perforated paediatric appendicitis include an abscess, loculated or complex intraperitoneal fluid, an appendicolith, dilated bowel and thickening of the terminal ileum, all of which demonstrate high specificity but low sensitivity. The high specificity of ultrasound indicates that it is a useful diagnostic tool to rule out perforated appendicitis and differentiate it from non‐perforated appendicitis in children.